Non Coding Region dan Amino Terminus Gen Polimerase Asidik Virus Avian Influenza Subtipe H5N1 Asal Hewan Indonesia - Yuniati Kencana, Gusti Ayu; Asmara, Widya; Rangga Tabbu, Charles; Kade Mahardika, I Gusti Ngurah (Jurnal Veteriner, 2010)
The knowledge on the species adaptation factor of avian influenza virus of H5N1 subtype (AIV H5N1)is very important as a signal for the emergence of a new strain with pandemic potential. This research wasconducted to find out the sequence variation of the Non-Coding Region (NCR) and Coding Region (CR) of 5’-terminal cRNA of the polymerase acidic (PA). Total RNA from twenty six (26) avian influenza virussubtype H5N1 isolates were amplified using reverse-transcriptase-polymerase chain reaction (RT-PCR)with a universal forward primer for influenza virus and specifically designed backward primers. Nineteen(19) gene fragments of PA could be amplified. RT-PCR products were sequenced and analyzed using Mega4 software. The length of NCR of PA gene was found to be 24 bases and conserved. A/T composition of PANCR was 58.3%. Species and geographical specificity could not be found in the genetic distance, the aminoacid polymorphism, as well as the phylogenetic analysis of the CR. RNA sequencing is discussed andrecomended to be studied further.
Keywords: Non coding region, amino terminus gen PA , avian influenza, H5N1, Indonesia